Spillover Effects of Oil Price Volatility on Pakistan’s Agricultural Sector - Sadaf, Mamona; Rashid, Abdul; Rehman, Hafeez ur; Hassan, Nadia (Pakistan Journal of Humanities and Social Sciences, 2025)
Surge in the prices of oil and food has led to the analysis for the volatility spill over between agriculture commodity market and crude oil market. Returns from major agriculture commodities from Pakistan and crude oil have been taken for the post crisis period as 2006M1: 2013M13 for the available data. Different extensions of GARCH model have been employed to see the volatility between the prices in either markets. Causality in variance test is used to examine the volatility spillover between the markets. No spillover effect has been found between both of the markets in case of Pakistan. However, long run relationship for shocks transmission between commodity and oil returns is depicted through VAR analysis.